Pay, talk or 'whip' to conserve forests: Framed field experiments in Zambia. (April 2020) - Ngoma, Hambulo; Hailu, Amare Teklay; Kabwe, Stephen; Angelsen, Arild
Highlights: Deforestation averaging 167, 000–300, 000 ha per year remain a challenge in Zambia. Different polices have been proposed to contain forest loss. But, there is limited evidence on their effectiveness. We conducted framed field experiments to test the impacts of three forest conservation policy instruments on harvest rates. Community forest management and payments for environmental services to individuals led to more forest conservation. Thus, both monetary and non-monetary motives matter for forest conservation. Abstract: Despite many efforts to conserve tropical forests, high rates of deforestation and forest degradation continue, threatening the products and environmental services they supply. We conducted framed field experiments (FFEs) in Zambia to test, ex-ante, the impacts of different conservation policies: community forest management (CFM), command and control (CAC), and two versions of payments for environmental services (PES). Our FFEs mimicked how local dwellers use forests in real life. Relative to open access (OA), PES to individuals reduced harvest by 15 percentage points (pp) while CFM reduced harvest rates by 8 pp. We conjecture that free and easy-riding, combined with uncertainty on how others will reciprocate, dampens the positive effects of group-based PES. Impatience and risk-loving among participants significantly increased harvest rates while pro-social behavior (altruism) was associated with more pro-conservation. We conclude that conservation outcomes might be achieved by combinations of CFM and individual PES, by which individual households receive clear material benefits that compensate for their reduced forest use.